2018
DOI: 10.1016/j.bjm.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Removal and killing of multispecies endodontic biofilms by N -acetylcysteine

Abstract: Removal of bacterial biofilm from the root canal system is essential for the management of endodontic disease. Here we evaluated the antibacterial effect of N-acetylcysteine (NAC), a potent antioxidant and mucolytic agent, against mature multispecies endodontic biofilms consisting of Actinomyces naeslundii, Lactobacillus salivarius, Streptococcus mutans and Enterococcus faecalis on sterile human dentin blocks. The biofilms were exposed to NAC (25, 50 and 100 mg/mL), saturated calcium hydroxide or 2% chlorhexid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 33 publications
2
34
0
1
Order By: Relevance
“…The thiol group of GSH may be a significant factor in the biofilm disruption process. Studies of another thiol-containing antioxidant N -acetylcysteine (NAC), at its intrinsic pH, showed that it destabilizes the biofilm matrix by chelating divalent cations (e.g., Ca 2+ and Mg 2+ ), inhibition of bacterial extracellular polysaccharide production, modulation of bacterial cell physiology and the impact on its metabolism (Olofsson et al, 2003; Zhao and Liu, 2010; Blasi et al, 2016; Choid et al, 2018). Whether the thiol group plays a greater role in biofilm disruption than the acidity of GSH has yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…The thiol group of GSH may be a significant factor in the biofilm disruption process. Studies of another thiol-containing antioxidant N -acetylcysteine (NAC), at its intrinsic pH, showed that it destabilizes the biofilm matrix by chelating divalent cations (e.g., Ca 2+ and Mg 2+ ), inhibition of bacterial extracellular polysaccharide production, modulation of bacterial cell physiology and the impact on its metabolism (Olofsson et al, 2003; Zhao and Liu, 2010; Blasi et al, 2016; Choid et al, 2018). Whether the thiol group plays a greater role in biofilm disruption than the acidity of GSH has yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that this interesting result may be related to a certain degree of antibacterial activity of NAC. NAC has been demonstrated to be a non-antibiotic compound that possesses antimicrobial activity towards endodontic pathogens and effectively decreases bacterial biofilm formation 24,25) . Microbial biofilms are bacterial communities with high cell densities in a matrix of hydrated extracellular polymeric substances, which are mostly composed of polysaccharides 26,27) .…”
Section: Discussionmentioning
confidence: 99%
“…Thus proper administration of GSH as an antimicrobial agent (either in the form of aerosol inhalation, spray, wound care gel, coatings on medical implants/equipment, oral therapy) will add a significantly to the ability to quickly treat the wide variety of P. aeruginosa biofilm infections, and also facilitate host tissue recovery. Another thiol-antioxidant, NAC (a precursor of GSH) has also shown great potential to disrupt multispecies endodontic biofilms, suggesting its potential use in root canal and dental plaque treatment ( Suk Choi et al, 2017 ). Similarly vitamin C, which is also naturally found in various food sources and is a major component of dietary vitamin supplements has recently been shown to kill drug-resistant Mycobacterium tuberculosis ( Vilcheze et al, 2013 ), supporting the notion that antioxidants represent a promising novel strategy to remove the biofilms of pathogenic bacteria and prevent biofilm infections in clinical settings.…”
Section: Discussionmentioning
confidence: 99%